Current Status of Production of Transgenic Livestock by Genome Editing Technology - Da Som Park; Soseob Kim; Deog-Bon Koo; Man-Jong Kang (The Korean Society of Animal Reproduction and Biotechnology, 2019)
The Transgenic livestock can be useful for the production of disease-resistant animals, pigs for xenotranplantation, animal bioreactor for therapeutic recombinant proteins and disease model animals. Previously, conventional methods without using artificial nuclease-dependent DNA cleavage system were used to produce such transgenic livestock, but their efficiency is known to be low. In the last decade, the development of artificial nucleases such as zinc-finger necleases (ZFNs), transcription activator-like effector nucleases (TALENs) and clustered regulatory interspaced short palindromic repeat (CRISPR)/Cas has led to more efficient production of knock-out and knock-in transgenic livestock. However, production of knock-in livestock is poor. In mouse, genetically modified mice are produced by co-injecting a pair of knock-in vector, which is a donor DNA, with a artificial nuclease in a pronuclear fertilized egg, but not in livestock. Gene targeting efficiency has been increased with the use of artificial nucleases, but the knock-in efficiency is still low in livestock. In many research now, somatic cell nuclear transfer (SCNT) methods used after selection of cell transfected with artificial nuclease for production of transgenic livestock. In particular, it is necessary to develop a system capable of producing transgenic livestock more efficiently by co-injection of artificial nuclease and knock-in vectors into fertilized eggs.